Quantitative determination and contamination pattern of perchlorate in tea by ultra performance liquid chromatography and tandem mass spectrometry. (15th February 2019) - Liu, Yan; Sun, Hezhi; Zhou, Li; Luo, Fengjian; Zhang, Xinzhong; Chen, Zongmao
Highlights: An efficient UPLC-MS/MS method for the determination of perchlorate in tea is established. The comparison of purification efficiency between Cleanert PWAX SPE and others is done. Perchlorate residue in dark tea is found higher than that in black tea or green tea. Perchlorate in tea accumulates along with the growth of tea leaves. Other pollutant sources of perchlorate should exist during planting process. Abstract: Perchlorate causes great health concerns for its inhibition on the iodide intake of human. However, the contamination pattern of perchlorate in tea remains unclear although tea is substantially consumed worldwide. Thus, the present study established an efficient method using ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) in combination with external standard method, and further lucubrated the contamination level of perchlorate in made tea, fresh tea leaves, along with the waters and soils from tea gardens. Fresh tea leaves with higher maturity generally contains more perchlorate. The observation explains well why the residual of perchlorate in dark tea is generally higher than that in black tea or green tea from the perspective of raw material. In consideration of the ubiquitous existence of perchlorate in waters and soils from tea gardens, perchlorate might accumulate in tea leaves via soil. This study not only provides an alternative quantification method of perchlorate when the isotope internal standard is out of stock, but also illuminates the contamination pattern of perchlorate in tea from planting process.